The usefulness of hand washing during field training to prevent acute respiratory illness in a military training facility. Issue 30 (July 2018) - Kim, Ho Seung; Ko, Ryoung Eun; Ji, Misuk; Lee, Ju-Hyung; Lee, Chang-Seop; Lee, Hyun
Abstract : Abstract: Hand washing plays a key role in preventing respiratory infection in many clinical settings. However, its effectiveness in preventing acute respiratory illness (ARI) during field training in military training facilities has been not studied. A quasi-interventional study was performed to evaluate the prevalence of ARIs over 4 weeks in a Korean army training center in South Korea from January 2009 to February 2009. A total of 1291 recruits participating in military training for 4 weeks were randomly distributed to 2 battalions (one with 631 and the other with 660). After noticing there is a difference between the 2 battalions in terms of the development of ARIs at the end of 2 weeks of training, we conducted interviews with the battle commanders to determine factors that may be related to one battalion having a higher incidence of ARI. Thereafter, we performed an intervention, which consists of instructing the battalion having a higher incidence of ARI to implement field hand washing from the third week. Following the intervention, we compared the cumulative rate of ARI during 4 weeks of training. The interviews revealed that there were no major differences between the 2 battalions in terms of the training schedules, living environments, or indoor hand washing methods. However, there was difference in terms of hand washing during field training for the first 2 weeks; whereas one battalion (the early hand washing group) implemented hand washing during field training starting in the first week, the other battalion did not implement hand washing for the first 2 weeks but instead began in the third week (the late hand washing group). The cumulative incidence rate of ARI during 4 weeks of training was significantly lower in the early hand washing group (13.0%, 95% confidence interval [CI]: 10.6%–15.9%) than in the late hand washing group (28.0%, 95% CI, 24.7%–31.5%). Our study suggests that outdoor hand washing during field training may be an effective precaution for reducing ARI incidence among recruits participating in military training.